(untitled) (Research, Society and Development, 2021)
The teaching of physics in Brazil has some limitations regarding the use of innovative methodologies, it is constantly pointed out that physics is approached from a traditional teaching methodology, a methodology that is widely discussed and pointed out as problematic for learning. Thus, the following article presents a narrative literature review on the influence of the capitalist social model on physics education, where it seeks to discuss the issues surrounding the current physics teaching and seek its direct or indirect relationship with the capitalist model of society presented by Karl Marx, to present a debate on the influence of this model on the school’s goals, on the type of man and citizen that this school, inserted in the capitalist model, seeks to form and on the pedagogical trends used within the current school and in the teaching of physics. Bringing as a result a reflection on the problems that affect students, teachers and that are structured from this model of society.